2021
DOI: 10.1021/acs.jpcc.1c05452
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of Monoclinic FeNbO4: Bulk Properties and Water Dissociation at the (010), (011), (110), and (111) Surfaces

Abstract: Monoclinic and orthorhombic FeNbO4-based materials have been developed for many applications, including hydrogen sensors and solid oxide electrolysis cell (SOEC) electrodes. Here, we have employed density functional theory (DFT) calculations to investigate the bulk and surface properties of the monoclinic FeNbO4 structure, as well as water adsorption and dissociation on its pristine surfaces. Our calculations show that the high-spin state Fe3+ cations have a relatively smaller Bader charge than the Nb5+ cation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 55 publications
(79 reference statements)
1
10
0
Order By: Relevance
“…Figure 5 shows an illustrative scheme that helps elucidate the change in magnetic ordering and the contribution of each interaction. Figure 5 a shows a net AFM configuration in the structure as already reported in the literature for m-FeNbO 4 [ 10 ]. This configuration contains FM interactions associated with Fe-O-Fe interactions and AFM interactions associated with Fe chains mediated by Nb, resulting in a liquid AFM order.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…Figure 5 shows an illustrative scheme that helps elucidate the change in magnetic ordering and the contribution of each interaction. Figure 5 a shows a net AFM configuration in the structure as already reported in the literature for m-FeNbO 4 [ 10 ]. This configuration contains FM interactions associated with Fe-O-Fe interactions and AFM interactions associated with Fe chains mediated by Nb, resulting in a liquid AFM order.…”
Section: Resultssupporting
confidence: 60%
“…FeNbO 4 is a polymorphic compound that crystallizes in three different crystalline phases depending on the annealing temperature [ 1 ].Considered an n-type semiconductor, it has a narrow bandgap of 1.81–2.25 eV [ 2 , 3 ], making it attractive for multipleapplications, e.g., as a photocatalyst [ 4 , 5 ], due to its excellent visible light activity attributed to the higher energy levels of the Nb 4d orbital;in gas sensors [ 3 ], capacitors [ 6 ], and lithium-ion batteries [ 7 , 8 ]; and as an anode material in solid oxide fuel cells (SOFCs) [ 9 ].The most stable phase, under ambient conditions, has monoclinic symmetry (m-FeNbO 4 , space group P2/c) and is obtained at temperatures below 1085 °C [ 10 ]. Its structure has ordered cations, with both Fe 3+ and Nb 5+ forming regular octahedra, coordinated by six oxygen ions, forming zig-zag chains of FeO 6 and NbO 6 (see Figure 1 a) [ 10 , 11 ]. A crystal structure with orthorhombic symmetry (o-FeNbO 4 , Pbcn space group) is formed in the temperature range of 1085 to 1380 °C [ 12 ].Unlike the m-FeNbO 4 phase, above 1100 °C, the distribution of cations in this structure becomes disordered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is obvious that (010) surface with Co-O terminated exhibits the lowest surface energy of 0.49 J m À2 , which is the thermodynamically favorable and prior exposing facet for catalytic reactions. 53,54 In this work, Co-O terminated (designated as 010Co) and W-O terminated (designated as 010W) 010 surfaces were applied to investigate the catalytic activity of CoWO 4 to identify the effect of distorted [WO 6 ] octahedral framework. The 010W surface exhibits a higher surface energy of 1.35 J m À2 compared to the 010Co surface.…”
Section: Resultsmentioning
confidence: 99%
“…In previous work, 23 we have employed calculations based on the density functional theory (DFT) to study the bulk and surface properties of m -FeNbO 4 . Due to the disorder of the cations in the o -FeNbO 4 phase, it is more difficult to create a computational model to simulate its behaviours and properties, which is presumably the reason why few computational studies have been reported on the orthorhombic phase.…”
Section: Introductionmentioning
confidence: 99%